Voix du Sud : étude de trois autobiographies de femmes esclaves - Dominique Aurélia (Transatlantica)
This essay examines the presence of the half-muted and marginalized women slaves’ voices which nevertheless inform the audience of the time as well as the contemporary scholar on their desire to inscribe their being within the public sphere as they question the issue of identity and emancipation through their texts. Beyond the pro-abolitionist debate context, they speak as true and free human beings living in a post-slavery society.